Superradiant emission regimes of the system of stationary oscillators - Kuklin, V.M.; Litvinov, D.N.; Sporov, A.E. (Вопросы атомной науки и техники, 2017)
The mathematical model of superluminescence of a finite system of nonlinear oscillators is considered. With each oscillator generating its own field, the oscillators interact through integral field of radiation. The influence of nonlinearity of oscillators due to relativistic effects is taken into account. Characteristics of the synchronization process are discussed. Regimes of field generation under conditions of radiation into an external space are considered. The influence of the energy loss due to external radiation on the generation efficiency is discussed.